Versatile transformations of hydrocarbons in anaerobic bacteria: substrate ranges and regio- and stereo-chemistry of activation reactions† - Jarling, René; Kühner, Simon; Basílio Janke, Eline; Gruner, Andrea; Drozdowska, Marta; Golding, Bernard T.; Rabus, Ralf; Wilkes, Heinz (Frontiers in Microbiology, 2015)
Anaerobic metabolism of hydrocarbons proceeds either via addition to fumarate or by hydroxylation in various microorganisms, e.g. sulfate-reducing or denitrifying bacteria, which are specialized in utilizing n-alkanes or alkylbenzenes as growth substrates. General pathways for carbon assimilation and energy gain have been elucidated for a limited number of possible substrates. In this work the metabolic activity of 11 bacterial strains during anaerobic growth with crude oil was investigated and compared with the metabolite patterns appearing during anaerobic growth with more than 40 different hydrocarbons supplied as binary mixtures. We show that the range of co-metabolically formed alkyl- and arylalkyl-succinates is much broader in n-alkane than in alkylbenzene utilizers. The structures and stereochemistry of these products are resolved. Furthermore, we demonstrate that anaerobic hydroxylation of alkylbenzenes does not only occur in denitrifiers but also in sulfate reducers. We propose that these processes play a role in detoxification under conditions of solvent stress. The thermophilic sulfate-reducing strain TD3 is shown to produce n-alkylsuccinates, which are suggested not to derive from terminal activation of n-alkanes, but rather to represent intermediates of a metabolic pathway short-cutting fumarate regeneration by reverse action of succinate synthase. The outcomes of this study provide a basis for geochemically tracing such processes in natural habitats and contribute to an improved understanding of microbial activity in hydrocarbon-rich anoxic environments.